PENINGKATAN PROSES DAN HASIL BELAJAR SENI BUDAYA DAN PRAKARYA (SBDP) MENGGUNAKAN MODEL PEMBELAJARAN DIRECT INSTRUCTION PADA SISWA KELAS IV DI SDN 143/VIII TELUK KEMBANG JAMBU KECAMATAN TEBO ULU - Amisah Istiqomah, Tri Wera Agrita, Randi Eka Putra, Opi Andriani (Jurnal Tunas Pendidikan, 2023)
The problem in this study is the low student learning outcomes in SBdP learning, the teacher’s lack of attention to the material or learning concepts that should be delivered. This resulted in the low process and learning outcomes of students in class IV SDN 143/VIII Teluk Kembang Jambu, Tebo Ulu District. This research is a classroom action research with simple qualitative and quantitative approach. The research subjects were fourth grade students, which amounted to 30 people. This research consists of two cycles. This research was carried out in the second semester of the 2021/2022 academic year at SDN 143/VIII Teluk Kembang Jambu Tebo Ulu District. This research data was collected through observations, test results, photos and documentation. The results of research data analysis show that using the Direct Instruction Model can improve the process and learning outcomes of arts, culture and crafts (SBdP) in the fourth grade of SDN 143/VIII Teluk Kembang Jambu. Seen from the process of implementing learning carried out by the teacher in cycle I 80% and in cycle II it became 84.61%, and during the student learning process in cycle I 62% and in cycle II it becomes 80.63%. The same thing is also seen in student learning in the first cycle is 69.6%, and in the second cycle it becomes 83.6%. Then classroom action research in the use of Direct Instruction Model in learning arts, culture and crafts (SBdP) can improve the process and student learning outcomes.